CHALLENGES FOR RUSSIAN UNIVERSITY AND SCHOLARS - Irina B. Nazarova (Moscow Polytechnic University, 2016)
Changes in the Russian system of higher education presented new challenges to universities in terms of their achievements and to professional scholars as well. Scholars forced to become muchmore active both in teaching and research. They have to publish more articles and research papers in prestigious foreign journals in English. They are induced to improve their skills or give way to those who are younger, have experience in leading educational and research institutions, or greater in academic achievement.The paper analyzes the strategic documents of the leading Russian universities, annual reports on the implementation of development programs.Russian scholars mostly write in Russian, read and cite articles of Russian-language authors. There were 89.9 articles per 100 persons in journals indexed in the database of the Russian Science Citation Index, 4.1 articles per 100 persons in the Web of Science, 5.3 articles per 100 persons in Scopus in 2013. The leading universities are intended to increase by 5 the number of articles in the foreign bases by 2020.On the one hand organizational culture and the principles of academic management may offer opportunities for development, gaining new competences, participating in contests and research. On the other hand the current situation can impose restrictions and provoke a teacher on the informal practices.